2016
DOI: 10.1002/clc.22659
|View full text |Cite
|
Sign up to set email alerts
|

Direct oral anticoagulant use in nonvalvular atrial fibrillation with valvular heart disease: a systematic review

Abstract: Direct oral anticoagulants (DOACs) are indicated for stroke prevention in patients with nonvalvular atrial fibrillation (NVAF), which, according to the American College of Cardiology/American Heart Association/Heart Rhythm Society atrial fibrillation (AF) guidelines, excludes patients with rheumatic mitral stenosis, a mechanical or bioprosthetic heart valve, or mitral valve repair. However, the data regarding use of DOACs in AF patients with other types of valvular heart disease (VHD) are unclear. We aimed to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 16 publications
(26 reference statements)
0
14
0
3
Order By: Relevance
“…Several studies have examined the effectiveness and safety of NOAC vs warfarin in AF patients with VHD, primarily in patients with EHRA Type 2 VHD 25‐32 . Meta‐analyses of post hoc analyses of previous randomised trials examining NOAC vs warfarin in AF patients with VHD showed that when pooling the results there was a reduced risk of thromboembolism in the NOAC group and no difference in the risk of major bleeding 33‐36 . However, in several comparative analyses based on real‐world data, the benefits of NOAC compared with warfarin were inconsistent 25‐28,32 .…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have examined the effectiveness and safety of NOAC vs warfarin in AF patients with VHD, primarily in patients with EHRA Type 2 VHD 25‐32 . Meta‐analyses of post hoc analyses of previous randomised trials examining NOAC vs warfarin in AF patients with VHD showed that when pooling the results there was a reduced risk of thromboembolism in the NOAC group and no difference in the risk of major bleeding 33‐36 . However, in several comparative analyses based on real‐world data, the benefits of NOAC compared with warfarin were inconsistent 25‐28,32 .…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4] Large randomized controlled trials (RCTs) and systematic reviews investigating have shown that DOAC therapy is not inferior to warfarin in the prevention of stroke and systemic embolism, and that it significantly reduces hemorrhagic complications, especially intracranial hemorrhage (ICH) in patients with nonvalvular AF. [5][6][7][8][9][10] In subgroup analyses of LVSD patients in the RE-LY (dabigatran), ROCKET-AF (rivaroxaban), and ARISTOTLE (apixaban) trials, researchers found similar results, with no significant difference between HF patients with preserved or reduced ejection fractions. [11][12][13] However, these RCTs excluded many patients that we often see in actual medical practice, including patients on anticoagulation therapy for indications other than AF, patients with significant renal dysfunction, and patients with a history of gastrointestinal (GI) bleeding and anemia, valvular heart disease, and indications for anticoagulation besides AF.…”
Section: Introductionmentioning
confidence: 94%
“…Patients with left ventricular systolic dysfunction (LVSD) often have other comorbid conditions that lead to an increased risk of stroke, including atrial fibrillation (AF), which itself is an indication for long‐term anticoagulation . Large randomized controlled trials (RCTs) and systematic reviews investigating direct oral anticoagulants (DOACs), such as the Randomized Evaluation of Long‐Term Anticoagulation Therapy (RE‐LY), Apixaban for Reduction in Stroke and Other Thromboembolic Events in Atrial Fibrillation (ARISTOTLE), Rivaroxaban Once Daily Oral Direct Factor Xa Inhibition Compared With Vitamin K Antagonism for Prevention of Stroke and Embolism Trial in Atrial Fibrillation (ROCKET‐AF), and Effective Anticoagulation With Factor Xa Next Generation in Atrial Fibrillation–Thrombolysis In Myocardial Infarction 48 (ENGAGE AF‐TIMI 48) trials, have shown that DOAC therapy is not inferior to warfarin in the prevention of stroke and systemic embolism, and that it significantly reduces hemorrhagic complications, especially intracranial hemorrhage (ICH) in patients with nonvalvular AF . In subgroup analyses of LVSD patients in the RE‐LY (dabigatran), ROCKET‐AF (rivaroxaban), and ARISTOTLE (apixaban) trials, researchers found similar results, with no significant difference between HF patients with preserved or reduced ejection fractions …”
Section: Introductionmentioning
confidence: 99%
“…48,50 Fortunately, subgroup analyses of the trial participants of the 4 major Phase III trials comparing warfarin to DOACs found that DOACs can be safely used in patients with forms of VHD such as aortic stenosis, aortic regurgitation and mitral regurgitation. 51,52 DOACs may therefore prove to be as effective as warfarin in patients with VHD, which will positively impact RHD care in SSA. Consequently, the efficacy of rivaroxaban is being compared to warfarin in patients with RHD and AF at high risk of stroke in the INVICTUS trial, an international, multicentre, randomized open-label trial that has enrolled >25% of its participants (1150) from 14 SSA countries 53 (Table 1).…”
Section: Anticoagulation In Af and Valvular Heart Diseasementioning
confidence: 99%